Collaborative strategy: Creating inclusive school-based guidance and counseling services - Sri Maullasari (SMARATUNGGA: JURNAL OF EDUCATION AND BUDDHIST STUDIES, 2021)
The purpose of this study was to describe collaborative strategies in creating inclusive school-based guidance and counseling services. Strengthening Inclusive Education required the role of all parties in educational institutions, including guidance and counseling. This study used the library research method. This literature study was related to the object of writing, which was inclusive guidance and counseling services. Every individual with special needs, both permanent and temporary, has different learning barriers and needs. School counselors were uniquely positioned to collaborate with stakeholders and identify each student's critical resources and support systems to achieve academic and socio-emotional success. Collaboration was the basis between the school and parents, and other experts to systematically, consistently, and sustainably.